A study on determinants of bank net interest margin in Malaysia / Nurhidayu Md Saad - Md Saad, Nurhidayu (Faculty of Business and Management, 2010)
This paper studies empirically the determinants of bank net interest margin in Malaysia from 2005 to 2009. A commercial bank that has been selected is Public Bank Berhad. Most study has follows the basic theoretical model of net interest margin proposed by Ho and Saunders (1981) and its extension proposed by Maudos and Guevara (2004) but in this study has follow the model that has modified from Kaiguo Zhou (2008). The study also indicates the determinants of net interest margins in Malaysia include average operating costs, credit risk that measure by loan ratio and interest rates or base lending rates. According to the overall results in this study it indicates the most independent variables are the most give an impact to the net interest margin (NIM) is average operating cost (AOC). It shows a positive and significance relationship between both variables. While credit risk that measure by loan ratio has negative and significance relationship. The other independent is base lending rate, according to the result it shows a positive relationship but don’t have a significance relationship with the NIM in Public Bank Berhad.